2018
DOI: 10.1111/iwj.12848
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐incision negative pressure therapy to reduce groin wound infections in vascular surgery: a randomised controlled trial

Abstract: Groin wound infections pose a major problem in vascular surgery. Closed-incision negative pressure therapy (ciNPT) was especially designed for the management of incisions at risk of surgical site infections. The aim of this study was to investigate whether ciNPT is able to reduce the incidence of wound infections after vascular surgery. Data on 132 consecutive patients, scheduled for vascular surgery with a longitudinal femoral cutdown, were collected prospectively. All patients were randomised either to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 32 publications
(47 reference statements)
1
46
2
Order By: Relevance
“…Two studies were at high risk of outcomes assessment bias as the outcomes assessments were not blinded. 11,18 Assessment bias was low in all five published manuscripts 3,11,15,16,18 compared to the published abstract which did not provide sufficient information to correctly make an assessment. 17 Three studies 11,16,18 were low risk for selective reported, but it was unclear for the remaining three studies (Table 3).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Two studies were at high risk of outcomes assessment bias as the outcomes assessments were not blinded. 11,18 Assessment bias was low in all five published manuscripts 3,11,15,16,18 compared to the published abstract which did not provide sufficient information to correctly make an assessment. 17 Three studies 11,16,18 were low risk for selective reported, but it was unclear for the remaining three studies (Table 3).…”
Section: Resultsmentioning
confidence: 94%
“…Of the six studies, two reported no device failures or adverse effects of the device. 11,15 One study reported that one patient had the device removed early owing to an inability to achieve an adequate seal postoperatively. 16 Three studies did not include information on device failure or adverse effects of the device.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations